ETNOBOTANI PANDAN (PANDANACEAE) DI TAMAN NASIONAL BUKIT DUABELAS, JAMBI - Dimas Prasaja; Muhadiono Muhadiono; Iwan Hilwan (Research Center for Biology-Indonesian Institute of Sciences, 2015)
This research was aimed to study ethnobotany and the diversity of Pandanaceae that utilized by the people of Orang Rimba tribe who lives in Bukit Duabelas National Park, Jambi. The results of this study showed there were six species of two genera (Benstonea and Pandanus)that were used for habitual and religion activities of those tribes. Only four species were used for crafts, especially mat and wallets (sumpit):Pandanus furcatus Roxb.; Pandanus labyrinthicus Kurz ex Miq.; Pandanus immersus Ridl.; and Benstonea atrocarpa (Griff.) Callm. & Buerki. Two species were used as a ceremony’s complement materials and tribe’s rituals: Pandanus labyrinthicus Kurz ex Miq. (ritual of marriage), and Benstonea atrocarpa (Griff.) Callm. & Buerki to kiding (the procession before the rice planting season begins).Only one species that was used as a material for the house’s or cottage’s roof, Benstonea kurzii (Merr.) Callm. & Buerki. Leaves were the part of the plant which used for the Orang Rimba daily needs.The skill for making handicraft were obtained iterally from generations. The population of pandan assumed to be decreased without effort for the cultivation and conservation.